Nutrition transition and dietary energy availability in Eastern Europe after the collapse of communism - Ulijaszek, S; Koziel, S (Elsevier, 2007)
After the economic transition of the late 1980s and early 1990s there was a rapid increase in overweight and obesity in many countries of Eastern Europe. This article describes changing availability of dietary energy from major dietary components since the transition to free-market economic systems among Eastern European nations, using food balance data obtained at national level for the years 1990-92 and 2005 from the FAOSTAT-Nutrition database. Dietary energy available to the East European nations satellite to the former Soviet Union (henceforth, Eastern Europe) was greater than in the nations of the former Soviet Union. Among the latter, the Western nations of the former Soviet Union had greater dietary energy availability than the Eastern and Southern nations of the former Soviet Union. The higher energy availability in Eastern Europe relative to the nations of the former Soviet Union consists mostly of high-protein foods. There has been no significant change in overall dietary energy availability to any category of East European nation between 1990-1992 and 2005, indicating that, at the macro-level, increasing rates of obesity in Eastern European countries cannot be attributed to increased dietary energy availability. The most plausible macro-level explanations for the obesity patterns observed in East European nations are declines in physical activity, increased real income, and increased consumption of goods that contribute to physical activity decline: cars, televisions and computers.